Depth-dependent geochemical and microbiological gradients in Fe(III) deposits resulting from coal mine-derived acid mine drainage - Brantner, Justin S.; Haake, Zachary J.; Burwick, John E.; Menge, Christopher M.; Hotchkiss, Shane T.; Senko, John M. (Frontiers in Microbiology, 2014)
We evaluated the depth-dependent geochemistry and microbiology of sediments that have developed via the microbially-mediated oxidation of Fe(II) dissolved in acid mine drainage (AMD), giving rise to a 8-10 cm deep “iron mound” that is composed primarily of Fe(III) (hydr)oxide phases. Chemical analyses of iron mound sediments indicated a zone of maximal Fe(III) reducing bacterial activity at a depth of approximately 2.5 cm despite the availability of dissolved O2 at this depth. Subsequently, Fe(II) was depleted at depths within the iron mound sediments that did not contain abundant O2. Evaluations of microbial communities at 1 cm depth intervals within the iron mound sediments using “next generation” nucleic acid sequencing approaches revealed an abundance of phylotypes attributable to acidophilic Fe(II) oxidizing Betaproteobacteria and the chloroplasts of photosynthetic microeukaryotic organisms in the upper 4 cm of the iron mound sediments. While we observed a depth-dependent transition in microbial community structure within the iron mound sediments, phylotypes attributable to Gammaproteobacterial lineages capable of both Fe(II) oxidation and Fe(III) reduction were abundant in sequence libraries (comprising ≥20% of sequences) from all depths. Similarly, abundances of total cells and culturable Fe(II) oxidizing bacteria were uniform throughout the iron mound sediments. Our results indicate that O2 and Fe(III) reduction co-occur in AMD-induced iron mound sediments, but that Fe(II)-oxidizing activity may be sustained in regions of the sediments that are depleted in O2.